2014
DOI: 10.1071/an13062
|View full text |Cite
|
Sign up to set email alerts
|

Pre-rigor carcass stretching counteracts the negative effects of high rigor temperature on tenderness and water-holding capacity – using lamb muscles as a model

Abstract: Abstract. High pre-rigor muscle temperature has negative consequences on quality and has been predominantly studied in the excised longissimus muscle of beef and lamb carcasses. There is little data on other muscles, the application in whole carcasses or potential amelioration techniques such as stretching. This study evaluated the effects of electrical stimulation, high pre-rigor temperature and stretching of lamb sides on quality traits and protein denaturation in four leg muscles [gluteus medius (GM), rectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 41 publications
(57 reference statements)
4
15
0
Order By: Relevance
“…Unfortunately, the number of carcasses tender-stretched was limited compared with samples in the normal pH-temperature range, but similar results were presented by Warner et al (2014b) and Kim et al (2014a) for sheep meat, while positive effects on WHC were also demonstrated in certain cases. The m. rectus femoris (RF) showed increased cooking losses , whereas no effect was recorded for m. longissimus lumborum (LL), and a clear positive effect was apparent for m. semimembranosus (SM) (Kim et al 2014a).…”
Section: Stretching and Heat-induced Tougheningsupporting
confidence: 54%
See 1 more Smart Citation
“…Unfortunately, the number of carcasses tender-stretched was limited compared with samples in the normal pH-temperature range, but similar results were presented by Warner et al (2014b) and Kim et al (2014a) for sheep meat, while positive effects on WHC were also demonstrated in certain cases. The m. rectus femoris (RF) showed increased cooking losses , whereas no effect was recorded for m. longissimus lumborum (LL), and a clear positive effect was apparent for m. semimembranosus (SM) (Kim et al 2014a).…”
Section: Stretching and Heat-induced Tougheningsupporting
confidence: 54%
“…Working on different muscles on sheep carcasses, Warner et al (2014b) found no shortening effect due to high rigor temperatures for m. gluteus medius (GM), m. semitendinosus (ST) and SM cuts. The RF cuts shortened, probably due to the anatomical position and/or muscle-fibre type of this muscle but surprisingly also showed increased tenderness (lower Warner-Bratzler shear force) for non-stretched muscle.…”
Section: Stretching and Heat-induced Tougheningmentioning
confidence: 99%
“…The decrease of water-holding capacity during summer could be attributed to the high muscle temperature recorded during this season. This finding was in accordance with those of Wang et al (2009) in broilers, Kim et al (2012) in cattle, and Warner et al (2014) in lambs. These previous authors reported that high temperature exposure induces excessive water loss from muscles.…”
Section: Effect Of Slaughter Season On the Different Parameterssupporting
confidence: 80%
“…Prevention against the toughening effect of shortening under high pre-rigor temperatures can be achieved by alternative carcass suspension (tenderstretching, superstretching, etc. ), or by tightly wrapping pre-rigor excised muscles to restrain shortening (Rosenvold et al 2008;Warner et al 2014b). In contrast, Kim et al (2012) observed no significant protective effect against toughening by restraining muscles exposed to high pre-rigor temperatures.…”
Section: Introductionmentioning
confidence: 90%
“…A square bipolar wave form was applied, providing 157-mA peakto-peak (28-33V) with a frequency of 14 Hz for a duration of 60 s. One side was then suspended from the tailbone and the other side from the aitchbone. For the side suspended by the aitchbone, the hindleg was tightly pulled down proximally, (closer to the ribs) and tied into the ventral (underside of body) surface, thus resulting in a stretching action being applied to the leg muscles; see photo in Warner et al (2014b) Then a temperature conditioning treatment was applied being: (i) Long/37 C -carcass placed in a 37 C vat of water for 4.5 h and then placed in a 2 C chiller (same conditions as Warner et al (2014b), (ii) Medium/37 C -carcass placed in a 37 C vat of water for 3 h and then placed in a 2 C chiller, (iii) Short/37 Ccarcass placed in a 37 C vat of water for 1.5 h and then placed in a 2 C chiller and (iv) Conventional 2 C -carcass placed into 2 C chiller where the carcass was placed directly into a chiller at 2 C after leaving the slaughter floor.…”
Section: Animals and Treatmentsmentioning
confidence: 99%